2020
DOI: 10.26434/chemrxiv.13414646.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Spatiotemporal Control of Supramolecular Polymerization and Gelation of Metal-Organic Polyhedra

Abstract: In coordination-based supramolecular materials such as metallogels, simultaneous temporal and spatial control of their assembly remains challenging. Here, we demonstrate that the combination of light with acids as stimuli allows for the spatiotemporal control over the architectures, mechanical properties, and shape of porous soft materials based on metal-organic polyhedra (MOPs). First, we show that the formation of a colloidal gel network from a preformed kinetically trapped MOP solution can be triggered upon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…The acid treatment was selected because it has been previously employed with success to detach N-donor ligands from Rh-MOPs in solution. 24 The acid-treated films were characterized through UV adsorption spectra, water contact angle (WCA), and AFM to analyze the chemical and morphological changes induced by acid treatment.…”
Section: Resultsmentioning
confidence: 99%
“…The acid treatment was selected because it has been previously employed with success to detach N-donor ligands from Rh-MOPs in solution. 24 The acid-treated films were characterized through UV adsorption spectra, water contact angle (WCA), and AFM to analyze the chemical and morphological changes induced by acid treatment.…”
Section: Resultsmentioning
confidence: 99%
“…As for sol−gel transition, techniques, i.e., rheological 25,26 and dynamic light scattering (DLS), 27,28 have been carried out to track such phase transition. The rheological measurement is normally used to determine the critical temperature for sol−gel transition based on the Winter criterion.…”
Section: Introductionmentioning
confidence: 99%
“…By controlling the coordination-driven self-assembly pathway of MOPs, recently we reported the successful fabrication of the linked MOP gels featuring hierarchical porous networks. 24,25 Instead of forming ordered frameworks like MOFs, the random crosslinking of MOPs as junctions with bisimidazole links results in the formation of colloids, followed by their further connections to form colloidal gels. In particular, we showed that the post-synthetic aging process induced the reorganization of crosslinked MOP networks inside the colloids and thus the control of extrinsic porosity.…”
Section: ■ Introductionmentioning
confidence: 99%